An ontology-driven approach for collaborative ubiquitous systems. (7th May 2010) - Sancho, G.; Villemur, T.; Tazi, S.
Ubiquitous computing environments are complex systems containing a great amount of heterogeneous devices and services available to users. Collaborative activities can benefit from the particular features offered by ubiquitous environments, such as the exploitation of context information. Applications have to be aware of this context and adapt to it. Moreover, such adaptation must be based on application semantics in order to better respond to user needs in any situation. This paper presents a semantic framework for the development of adaptive collaborative applications in ubiquitous computing environments. An ontology model, containing generic collaboration knowledge as well as domain-specific knowledge, is proposed in order to enable architecture adaptation and to support spontaneous and implicit sessions inside groups of humans and devices. The generic part of this model, called generic collaboration ontology (GCO) can be extended by domain-specific ontologies in order to use collaboration knowledge in applications of those domains.